2022
DOI: 10.1155/2022/9208172
|View full text |Cite|
|
Sign up to set email alerts
|

The Design of Psychological Education Intervention System in Universities Based on Deep Learning

Abstract: With the rapid development of Chinese society and economy as well as the deepening of the reform of the higher education management system and the change of employment mode of graduates, college students face various challenges of frustration and pressure in the areas of value and ethical concepts, interpersonal relationships, behavior, life, and employment. Some students who are relatively fragile psychologically are unable to bear the heavy pressure of frustration and challenges, and are prone to psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Among them, the system model is the core of the platform application, the system view is used to display the relevant data of the service platform, and the system controller is responsible for the information input and processing of the service platform. The layers of the system model, system view, and system controller cooperate to realize the visualization of the multidimensional network data set of the education service platform and the coordinated operation of various applications of the platform [8].…”
Section: System Overall Framework Designmentioning
confidence: 99%
“…Among them, the system model is the core of the platform application, the system view is used to display the relevant data of the service platform, and the system controller is responsible for the information input and processing of the service platform. The layers of the system model, system view, and system controller cooperate to realize the visualization of the multidimensional network data set of the education service platform and the coordinated operation of various applications of the platform [8].…”
Section: System Overall Framework Designmentioning
confidence: 99%
“…Even though it was not designed with education in mind, this paradigm has become the foundation for research on instructional technology. According to the findings of several types of research on management education aided by technology, factors such as perceived utility and perceived ease of use influence satisfaction levels but do not directly predict the effects of psychological education (Wang & Yang, 2022). It is made that discovery that the perceived ease of using technology is a good predictor of its adoption.…”
Section: The Factors That Contribute To the Success Of Management Edu...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%